PENGARUH MODEL GAME BASED LEARNING (GBL) MELALUI MONOPOLI PINTAR TERHADAP KEAKTIFAN BELAJAR SISWA MATA PELAJARAN SKI KELAS IV MI ISLAMIYAH SUMURGENUK - Mila Diya Istiqomah; Mahbub Junaidi; Nina Rohmatul Fauziyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the significant effect of the Game Based Learning (GBL) model through Smart Monopoly on the learning activeness of fourth-grade students in the subject of Islamic Cultural History (SKI) at MI Islamiyah Sumurgenuk. This research used a quantitative approach with a pre-experimental design (one group pretest-posttest design). The sample consisted of 25 fourth-grade students at MI Islamiyah Sumurgenuk. Data were collected through observation sheets and questionnaires. Data analysis used the Wilcoxon Signed Rank Test because the data were not normally distributed based on the Shapiro-Wilk test. The results showed that the average pretest score was 37.60 (80% of students in the Very Less Active category), and the posttest score increased significantly to 63.20 (an increase of 25.60 points or 68.1%). The Wilcoxon test results obtained Z = −4.344 with Asymp. Sig. (2-tailed) = 0.000 < 0.05, so H₀ was rejected and Hₐ was accepted. It can be concluded that there is a significant effect of the GBL model through Smart Monopoly on the learning activeness of fourth-grade students in the SKI subject at MI Islamiyah Sumurgenuk. These findings confirm that game-based learning innovations can be an effective solution to overcome low student learning activeness.